Prokaryotic community structure and key taxa in the Arabian Sea’s oxygen minimum zone - Li, Ding; Wang, Liping; Jiang, Fan; Zeng, Xiang; Xu, Qinzeng; Zhang, Xuelei; Zheng, Qiang; Shao, Zongze (Frontiers in Marine Science, 2024)
Microbial communities within oxygen minimum zones (OMZs) play crucial roles in the marine biogeochemical cycling. Arabian Sea (AS) has one of the largest OMZs among the global oceans, however, knowledge about the microbial ecology of the AS OMZ remained limited. In the present study, 44 water samples collected from six stations across the AS, spanning from the deep chlorophyll maximum (DCM) layer to 4000m depth were analyzed. High-throughput sequencing of 16S rRNA genes revealed the structural diversity of bacterial and archaeal communities, influenced primarily by depth and dissolved oxygen (DO) levels. Distinct community compositions were observed across different oxygen gradients, with shifts in the relative abundance of key taxa. Notably, Desulfosarcinaceae, UBA10353, Nitrospina, SUP05, Sva0996_marine_group, Microtrichaceae, and Nitrosopumilus emerged as bioindicator taxa in the AS hypoxic zones. Co-occurrence network analysis identified SAR324, Alteromonadaceae, and Sphingomonadaceae as keystone taxa. The spatial and depth-wise distribution patterns revealed that Desulfosarcinaceae was predominantly found in the hypoxic zones of the Arabian Sea, whereas UBA10353, Nitrospina, SUP05, Microtrichaceae and SAR324 were ubiquitous across AS, Bay of Bengal (BOB), and Eastern Tropical North Pacific (ETNP) OMZs, with OTU-level niche differentiation observed for the latter two. Functional profiling using FAPROTAX predicted higher metabolic potential for nitrogen and sulfur in the OMZ compared to other layers of the AS. Our findings provide valuable insights into the distribution, structure, and diversity of microbial communities in the AS OMZ, highlighting the ecological roles of key taxa in hypoxic environments. The established sequence database offers a foundation for further research into the complex interactions within these microbial ecosystems.